(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Bestlink College of the Philippines is one of the largest schools that need to monitor all equipment, but the staff has difficulty sorting and searching the logbook to find the equipment easily. The school can monitor their stocked products and keep an accurate record of the stockroom supplies. Bestlink College of the Philippines can organize and manpower needed to facilitate the inventory process. The inventory system tends to replace the best transaction with good and high-quality products in the school’s business and future growth because it will make any transaction hassle-free and effortless.The researchers used the systems development life cycle method as a process in which the researchers will complete the project. In system planning, the group will start to plan the things to do in the completion of the project. In the requirements analysis, the system analyst interviewed the client. The researchers will start to write down the things they encounter in the existing system. In system design, the programmer will start to jot down the codes and design the system, which may solve the problems. The problems that the researchers have gathered will be answered in the development of system implementation. The researchers will implement the proposed project to the client. The process that the researchers used in pilot conversion where the system willbe implemented in a particular branch. In system maintenance, the researchers will suggest if there is a need to update the system or the system itself needs to be updated. The login form is important to access the system. Two users can access the system, that is, the admin and the staff. After the users performed, the login will appear. This is where all transactions begin by filling up all the records. Book form has table records, n button update, edit button, and a delete button. Choices that which similar to the booklet and uniform forms are provided on the left side. In the account form, people who can access the system are visible. The registration button is also observed. In the registration form, the user can create an account to access the system by filling up all the blank spaces and choosing whether they logged in as an either admin or as a staff. The audit trail is where all the login and logout processes can be seen. The researchers will meet the expectations of the client, sorting the equipment will be fastened, decreasing time consumption by using the system, and resulting in a stronger and more improved security system.